Antireflux operation for vesicoureteral reflux in spina bifida patients - Momose, H (Hinyokika kiyo. Acta urologica Japonica, 1993)
A series of 32 patients with spina bifida, representing 50 renal units with vesicoureteral reflux (VUR), was treated with antireflux operation. All but one patient underwent ureteral reimplantation with Cohen's technique. Another patient was treated with bilateral Politano-Leadbetter's technique. The overall success rates were 92.0% by renal unit and 87.5% by case, with a mean follow-up period of 42.5 months. These results were comparable to those in the recent literature. Failure included recurrence of VUR in 3 patients. Another patient who had undergone unilateral reimplantation developed new occurrence of reflux in the contralateral ureter. Possible masking of contralateral VUR should be taken into consideration in patients with unilateral high grade VUR. We also emphasize the importance of continuing clean intermittent catheterization in a proper manner to be free of VUR postoperatively